ACCESSORY PLASMA FACTORS INVOLVED IN THE BACTERICIDAL TEST FOR TYPE-SPECIFIC ANTIBODY TO GROUP A STREPTOCOCCI : II. HUMAN PLASMA COFACTOR(S) ENHANCING OPSONIZATION OF ENCAPSULATED ORGANISMS - Stollerman, Gene H. (The Rockefeller University Press, 1963)
A study was made of the nature of the thermolabile plasma factors in human blood which promote the phagocytosis of Group A streptococci in vitro in the presence of optimal amounts of type-specific M antibody. The plasmas of individuals with strong opsonic activity (normal) were compared with those of some individuals whose opsonic activity was consistently weak (deficient). A general relationship was established between encapsulation of streptococci and the opsonic requirement for thermolabile plasma factor(s). Marked differences in phagocytosis of Group A organisms by human bloods were demonstrated with encapsulated strains only. Human bloods deficient in the cofactor required for opsonization of encapsulated streptococci (coopsonin) showed a normal rate of phagocytosis against all other organisms and particles studied. Furthermore, coopsonin-deficient bloods contained normal levels of four components of complement, of properdin, of lysozyme, and of direct bactericidal activity against several species of Gram-negative organisms and of E. coli bacteriophage. The independence of the streptococcal coopsonin from complement was also demonstrated by absorption of plasma with bentonite and with zymosan. Under appropriate conditions, the coopsonin was reduced without significant loss of complement. The data support the concept that the capsule of the streptococcus imposes an opsonic requirement for a plasma factor(s) which is present in varying amounts in human bloods and which appears to be independent of the complement system. The possibility that it is accessory to the latter components has not been excluded.